A qualitative analysis of Litsea fulva essential oils using comprehensive two-dimensional gas chromatography coupled with time-of-flight mass spectrometry - Khong, Heng Yen; Laily Din; Zuriati Zakaria; Nor Hadiani Ismail; Nor Zamzurina Ismail; Mohd Ambar Yarmo (Universiti Kebangsaan Malaysia, 2013)
A qualitative analysis of the individual compounds in Litsea fulva (locally known as ‘Medang’) essential oils was performed by comprehensive two-dimensional gas chromatography (GC × GC) coupled with time-of-flight mass spectrometer (TOF/MS) for the identification of the resolved peaks. Litsea fulva essential oil was found to contain 98 identifiable peaks with 32 compounds were identified with good matches. These compounds identified included 30 hydrocarbons, 22 alcohols, five acids, 16 ketones, five aldehydes, 12 esters, six ethers and two other compounds. The L. fulva leaf oil contained alcohols and ethers, with 34.09% and 24.38%, respectively. The major components of these oils were cis-Z-α-bisabolene epoxide (9.51%), trans-Z-α-bisabolene epoxide (8.36%), C13H20O2 (7.39%), longipinocarvone (5.68%), τ-Cadinol (4.24%), C15H24O (4.98%) and α-cadinol (3.95%). The study also showed that the comprehensive two-dimensional gas chromatography (GC × GC) is a better and more powerful separation tool in GC and an identification tool for analyzing complex volatile oils compared with the one-dimensional GC.